2017
DOI: 10.3389/fphys.2017.00447
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Remodeling in Response to Eccentric vs. Concentric Loading: Morphological, Molecular, and Metabolic Adaptations

Abstract: Skeletal muscle contracts either by shortening or lengthening (concentrically or eccentrically, respectively); however, the two contractions substantially differ from one another in terms of mechanisms of force generation, maximum force production and energy cost. It is generally known that eccentric actions generate greater force than isometric and concentric contractions and at a lower metabolic cost. Hence, by virtue of the greater mechanical loading involved in active lengthening, eccentric resistance trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
276
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(302 citation statements)
references
References 135 publications
(197 reference statements)
18
276
3
5
Order By: Relevance
“…Unlike muscle volume, which is highly dependent on total training volume, there are demonstrable differences between contraction type and alteration in fascicle length and pennation angle . To date, very few studies have compared the effect of isometric resistance training variations on muscle architecture; of those that have, results are equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike muscle volume, which is highly dependent on total training volume, there are demonstrable differences between contraction type and alteration in fascicle length and pennation angle . To date, very few studies have compared the effect of isometric resistance training variations on muscle architecture; of those that have, results are equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…Although the impact of ECC training on lean mass (LM) has been extensively studied, the findings are too varied to clearly affirm the superiority of ECC training . Recent meta‐analyses demonstrated that when matched for load or work, changes between ECC and CON training were found similar in regard to muscle hypertrophy . Considering fat mass (FM), the impact of ECC training remains poorly studied, without direct comparisons between ECC and CON training.…”
Section: Introductionmentioning
confidence: 99%
“… However, skeletal muscles may not necessarily grow to be the optimized shaped of the numerical examples because the complicated boundary condition is not taken into consideration in Section 3.1, and the difference of the contractile properties between different fusiform shapes is small as shown in Table . Skeletal muscles may grow to be some other fusiform shapes to pursue a better dynamic performance, eg, the dynamic performance in high‐power movements, eccentric loading, and concentric loading but not the static performance in proposed in Equation .…”
Section: Discussionmentioning
confidence: 99%